Green roof performance under malaysia tropical climates: a review - Nur Fitriah Isa; Hartini Kasmin; Norhaizura Yahya; Mustaqqim Abdul Rahim; Zuhayr Md Ghazaly (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Green roof system is one of sustainable approach for energy consumption reduction and improving the aesthetic value of the built environment. The system has been adopted by most of developed countries; and in Malaysia, research on green roof studies are quite evolving however the implementation of the system is slow due to some perceptions and obstacles. Green roof has potential on providing benefits such as reduction on the urban heat island effect, reduces temperatures, pollution and improves the attenuation of stormwater. This paper will highlights on a preliminary review of the implementation green roof system in Malaysia and explores the performances of Malaysian green roof in order to highlight the performance of green roof under tropical climatic conditions using local configurations.